TINGKAT CUSTOMER LOYALTY PADA PRODUK FASHION ONLINE - Arya Abhirakshantu Mp, Putu; Soelasih, Yasintha (Catholic University Musi Charitas, 2025)
Purpose This study examines the influence of online customer experience, perceived price, and product quality on customer loyalty, mediated by customer satisfaction, in the context of fashion products purchased via e-commerce platforms. Design/Methodology/Approach A quantitative survey was conducted among individuals who had purchased fashion products online. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) via SmartPLS 3. Findings The results show that online customer experience, perceived price, and product quality positively and significantly affect customer satisfaction. Customer satisfaction also partially mediates the relationship between these variables and customer loyalty. Practical Implications The findings highlight the importance of enhancing online experience, pricing strategies, and product quality to foster customer satisfaction and loyalty. Originality/Value This study offers empirical insights into the partial mediating role of customer satisfaction in e-commerce, enriching the understanding of consumer behavior in online fashion retail.